Subgame Perfect Implementation - Moore, John; Repullo, Rafael (Econometrica, 1988)
This paper examines the use of stage mechanisms in implementation problems and provides a partial characterization of the set of subgam e perfect implementable choice rules. It is shown that, in many economic environments, virtually an y choice rule can be implemented. To illustrate the power of this approach, the paper discusses a number of models in which it is possible to implement the first-best (although it wouldn't have been possible to do so without using stage mechanisms). The diversity of these models suggests that subgame perfect implementation may find wide application. Copyright 1988 by The Econometric Society.